Monitoring and Controlling System of Chopped Tobacco Dryer Using Fuzzy Logic Method - Bagus Budi Prayogo; Fachrudin Hunaini; Mohammad Muhsin (Muhammadiyah University, Sidoarjo, 2022)
Technological developments in post-harvest on the tobacco drying system which is a process of evaporation of water using heat energy or hot air flow aims to inhibit the growth of fungi and bacteria. The method of processing tobacco using the hot air flow method in the oven currently uses a temperature setting that is done manually and strict supervision must be carried out so that the results of the tobacco oven are not damaged. An automatic tobacco drying system can be an option so that the drying process can produce quality tobacco. By embedding the Fuzzy Logic Controller (FLC) method in the tobacco drying system, the temperature can be controlled by controlling the PWM which aims to turn the heater on and off. The tobacco drying oven system controls the oven to adjust the temperature according to the setting point of 35° and an error of 0.02% and reduces the moisture content to 25.6% remaining in the tobacco